Evaluación nutricional de los recursos naturales en la alimentación bovina en el Municipio de San Lucas, Michoacán - Villaseñor Álvarez, Alejandro (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The aim was characterized nutritional of natural resources in the bovine feeding in San Lucas Municipalitie, Michoacán State. Its monitored fiftheen sites, aditionally, its obteined dates for sea level on altitud. For estimated the quantify of biomass fodder its employed a methalic gris of 50 X 50 cm, its cut, identify and weigthed the samples of grasses, shrubs and fodder trees and your later taxonomic classification. Its taken samples for the grasses, shrubs and fodder trees by analysis chemical – proximal. The results of biomass fodder in the sites sampled was 910.66 ± 234.56 g/m2 and average of sea level on altitude 394.4 ± 54.62. The species of grasses identified was for importance and its nutritional values by % crude protein, organic matter, acid detergent fiber, tannines and phenols: Bouteloua spp, 3.74, 88.58, 37.04, 0.20 and 0.40; Aeschynomene americana (L.), 7.23, 92.87, 41.57, 0.24 and 0.90; and Melampodium americanum, 4.85, 89.15, 39.77, 0.42 and 0.74 respectively. For the trees and shrubs fodders was: Combretum farinosum, 10.68, 90.35, 23.82, 5.09 and 0.0; Mastichodentron capiri, 15.77, 91.47, 29.50, 0.0 and 0.73; Caesalpinia coriaria, 10.01, 96.63, 18.94, 2.67 and 12.36; Ziziphus amole, 14.38, 8.43, 91.57, 32.10, 11.29 and 2.85; Guazuma ulmifolia Lam, 12.13, 90.94, 29.65, 10.23 and 2.39; Cordia elaeagnoides; 15.12, 86.82, 25.53, 0.99 and 7.98, y Acacia farnesiana (fruit), 11.74, 94.16, 48.16, 24.22 and 3.68 respectively. Its concluded the importance that represented the natural resources in the bovine feeding under condition of dry tropic and mainly during dry period at that are summit the animals and be the only resource of nutriments in this particular period.

El objetivo del presente estudio fue caracterizar nutricionalmente los recursos naturales en la alimentación bovina en el Municipio de San Lucas, Mich.. Se muestrearon 15 sitios y se obtuvieron datos de la altitud sobre el nivel del mar. Para estimar la cantidad de biomasa forrajera se utilizó un cuadro metálico de 50 X 50 cm, se cortó, identificó y pesó las muestras de pastos, arbustos y árboles forrajeros y su posterior clasificación taxonómica. Se tomaron muestras de los pastos, arbustos y árboles forrajeros para su análisis químico – proximal. Los resultados de la biomasa forrajera de los sitios muestrados fue 910.66 ± 234.56 g/m2 en base fresca y un promedio de altitud sobre el nivel del mar 394.4 ± 54.62. Las especies de pastos y herbáceas identificadas fueron por orden de importancia y valores nutricionales de proteína cruda (%), materia orgánica (%), fibra detergente ácida (%), taninos (g/100) y fenoles (g/100): Bouteloua filiformes, 3.74, 88.58, 37.04, 0.20 y 0.40; Aeschynomene americana (L.), 7.23, 92.87, 41.57, 0.24 y 0.90; y Melampodium americanum, 4.85, 89.15, 39.77, 0.42 y 0.74 respectivamente. Para los árboles y arbustos forrajeros fueron: Combretum farinosum, 10.68, 90.35, 23.82, 5.09 y 0.0; Mastichodentron capiri, 15.77, 91.47, 29.50, 0.0 y 0.73; Caesalpinia coriaria, 10.01, 96.63, 18.94, 2.67 y 12.36, Ziziphus amole, 14.38, 91.57, 32.10, 11.29 y 2.85; Guazuma ulmifolia Lam, 12.13, 90.94, 29.65, 10.23 y 2.39; Cordia elaeagnoides, 15.12, 86.82, 25.53, 0.99 y 7.98, y Acacia farnesiana (vainas), 11.74, 94.16, 48.16, 24.22 y 3.68 respectivamente. Se concluye en la importancia que representan los recursos naturales en la alimentación de los bovinos bajo condiciones de trópico seco y principalmente durante el periodo de sequía al que están sometidos los animales y ser la única fuente de nutrimentos en este periodo particular.
Facultad de Medicina Veterinaria y Zootecnia. Maestría en Desarrollo Tecnológico en Sistemas de Producción Animal
Keywords: info:eu-repo/classification/cti/6; FMVZ-M-2007-0008; Pastos nativos; Árboles forrajeros; Valor nutricional; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5681